PROSES PENDAMPINGAN PEKERJA SOSIAL PADA BALAI REHABILITASI SOSIAL ANAK YANG MEMERLUKAN PERLINDUNGAN KHUSUS (BRSAMPK) RUMBAI PEKANBARU - Saniah Pane; Said Suhil Achmad; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examines the Assistance Process for Social Workers at theCenter for Social Rehabilitation of Children Requiring Special Protection (BRSAMPK)Rumbai Pekanbaru and in the mentoring process there are accompanying activities,teaching activities, directing activities, control activities and controlling activities. Thisstudy aims to describe the process of assisting social workers at the Center for theSocial Rehabilitation of Children in Need of Special Protection (BRSAMPK) RumbaiPekanbaru. This type of research is descriptive with a qualitative approach, in whichthe data collection process is carried out by interviewing 3 subjects, namely controlinformants, core informants 1, core informants 2 with documentation included. Theresults showed that the process of assisting social workers at the Center for SocialRehabilitation of Children in Need of Special Protection (BRSAMPK) RumbaiPekanbaru was running well with the implementation of accompanying activities,teaching, direction, control and supervision carried out by social workers with childrenaccording to the schedule and structure set out has been established.Key Words: Mentoring Process; Social Worker; BRSAMPK